Implementasi Metode Root Cause Analysis (RCA) untuk Mengendalikan Reject Produk NP Project di PT. XYZ - Sitompul, Mimi Aprija (Journal of Manufacturing in Industrial Engineering & Technology, 2024)
PT. XYZ is a company engaged in the electronics manufacturing industry located in the city of Batam, Riau Islands. One of the Departments of PT. XYZ is a Surface Mount Technology (SMT) Department that operates in the manufacture of Printed Circuit Board Assembly (PCBA). One of the products produced is the NP Project, this study aims to find out the largest type of rejection produced by the production line. The improvements made to control rejections in NP project products in this study use the Root Cause Analysis (RCA) method to find the root cause of reject problems that occur in NP products, After conducting the research it was found that the most dominant type of rejection is the gap component, Before conducting this study, the number of The rejection of the gap component was 9.39% after the research was carried out, the number of rejections decreased to 0.89%.